2015
DOI: 10.1523/jneurosci.1041-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Single-Trial Decoding of Visual Attention from Local Field Potentials in the Primate Lateral Prefrontal Cortex Is Frequency-Dependent

Abstract: Local field potentials (LFPs) are fluctuations of extracellular voltage that may reflect the physiological phenomena occurring within a volume of neural tissue. It is known that the allocation of spatial attention modulates the amplitude of LFPs in visual areas of primates. An issue that remains poorly investigated is whether and how attention modulates LFPs in executive brain areas, such as the lateral prefrontal cortex (LPFC), thought to be involved in the origins of attention. We addressed this issue by rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 61 publications
5
48
0
Order By: Relevance
“…As compared with our findings of decoding covert attentional shift to subsets of external stimuli, there are other recent studies decoding visuospatial attention directly from the intrinsically driven brain activity patterns evoked by attention6970717273. As our study demonstrates the possibility of seamlessly decoding human top-down processes, if a further refined grid-shaped line array is developed and combined with a more elaborated classification method, a recent study74 provides advances in extending previous studies of decoding visuospatial attention6970717273, which were limited to decoding up to four discrete locations/classes.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As compared with our findings of decoding covert attentional shift to subsets of external stimuli, there are other recent studies decoding visuospatial attention directly from the intrinsically driven brain activity patterns evoked by attention6970717273. As our study demonstrates the possibility of seamlessly decoding human top-down processes, if a further refined grid-shaped line array is developed and combined with a more elaborated classification method, a recent study74 provides advances in extending previous studies of decoding visuospatial attention6970717273, which were limited to decoding up to four discrete locations/classes.…”
Section: Discussionsupporting
confidence: 74%
“…As our study demonstrates the possibility of seamlessly decoding human top-down processes, if a further refined grid-shaped line array is developed and combined with a more elaborated classification method, a recent study74 provides advances in extending previous studies of decoding visuospatial attention6970717273, which were limited to decoding up to four discrete locations/classes. The authors found a neuronal signature of direct two-dimensional access to the spatial location of covert attention in macaque prefrontal cortex74.…”
Section: Discussionmentioning
confidence: 77%
“…To obtain the analytical signal from the preprocessed LFP data, we convolved it with 34 logarithmically spaced complex Morlet wavelets, with seven oscillations (Tallon‐Baudry, Bertrand, Delpuech, & Permier, ) and center frequencies ranging from 2.63 to 256 Hz (Hughes, Whitten, Caplan, & Dickson, ; Liebe, Hoerzer, Logothetis, & Rainer, ; Tremblay, Doucet, Pieper, Sachs, & Martinez‐Trujillo, ). Power was obtained from the squared magnitude of the analytical signal, while phase was derived from the angle between the real and complex parts.…”
Section: Methodsmentioning
confidence: 99%
“…Saccades have been shown to modulate LFPs in multiple brain areas, such as PFC (Tremblay et al, 2015) and visual cortex (Ito et al, 2011(Ito et al, , 2013Staudigl et al, 2017) cortices. In V1, both saccades and fixations have been found to elicit PC in the delta/theta and alpha/beta bands (Ito et al, 2011(Ito et al, , 2013.…”
Section: Origin Of Lfp Modulationsmentioning
confidence: 99%
“…Different circuit-level mechanisms will produce different population structures and it can be critical to know which structure is present when analysing data. For example, a common analysis approach is to train a decoder to predict key experimental variables during one epoch or context and use that decoder to interpret data from another epoch or context14454647. This approach is appropriate in the case of overlapping structure, but not for independent or orthogonal-but-linked structures.…”
mentioning
confidence: 99%